2009 International Conference on Management and Service Science 2009
DOI: 10.1109/icmss.2009.5301661
|View full text |Cite|
|
Sign up to set email alerts
|

Notice of Retraction: Analyzing Early Market Potential and Strategies for Carpooling in China: A Case Study of Wuhan

Abstract: Carpooling has been proven to be an effective Transportation Demand Management (TDM) measure by foreign practices and is developing rapidly as a form of public spontaneous behavior in most cities of China. After the questionnaire was designed with revealed preference (RP) survey method and stated preference (SP) survey method, the authors implemented an intercept survey within Wuhan to explore carpooling familiarity, response and market potential. This paper mainly focuses on the status and potential of carpoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Dynamic carpooling probably dates back to the early 1990s, but it has been successful only since 2012. As Friginal et al (2014) reported, recent studies carried out in China (Xin et al, 2009) have underlined an increasing interest in dynamic carpooling solutions, highlighting financial savings and traffic reduction as its main advantages. It is characterized by the possibility of organizing specific routes suddenly in exchange for the payment of a certain amount of money, thanks to the use of a mobile device with GPS and connected to a social network (Mallus et al, 2017).…”
Section: Dynamic Carpoolingmentioning
confidence: 99%
“…Dynamic carpooling probably dates back to the early 1990s, but it has been successful only since 2012. As Friginal et al (2014) reported, recent studies carried out in China (Xin et al, 2009) have underlined an increasing interest in dynamic carpooling solutions, highlighting financial savings and traffic reduction as its main advantages. It is characterized by the possibility of organizing specific routes suddenly in exchange for the payment of a certain amount of money, thanks to the use of a mobile device with GPS and connected to a social network (Mallus et al, 2017).…”
Section: Dynamic Carpoolingmentioning
confidence: 99%
“…However it is in the last 5 years when it has gained momentum in our society, specially in countries with high population density. For example, recent studies carried out in China [8], state the increasing interest of society in carpooling solutions, highlighting the cost saving and congestion reduction as the most important benefits. However, to address its dynamic decentralised deployment it is necessary to face some issues.…”
Section: Challenges Of Dynamic Carpoolingmentioning
confidence: 99%
“…However, in practice, users are rarely warned in case the other party delays since there is not a continuous monitoring of user location. This problem, identified as complex for carpooling [8], has been explored in European projects such as Eureka-Celtic WiSafeCar 3 from a dynamic perspective. This project focused on studying the real-time problems of carpooling such as the scheduling and automated allocation of users, taking into account unforeseen events.…”
Section: Scheduling the Meeting Pointmentioning
confidence: 99%
See 2 more Smart Citations